Being a 'Host' or a 'Journalist': Orientation to role on the ABC׳s Q&A. (March 2016) - Ames, Kate
Abstract: Broadcast nationally, Q&A is a television program promoted by the Australian Broadcasting Commission (ABC), Australia׳s national broadcaster as an 'adventure in democracy'. Previous academic study on the program has considered the program from a range of perspectives but this paper specifically examines the techniques used by Tony Jones, long-time host of Australian current affairs program Q&A, to facilitate panel discussion and interaction between members and the studio audience. This paper considers the way Jones is skilfully able to transition between the role of host and journalist, arguing that these are two quite different roles. The analysis also demonstrates the way in which the audience members in turn orient to the role Jones plays, and suggests that this occurs through familiarity with the show׳s formula and consistency of approach by Jones. Highlights: Analysis of a host׳s role in a talk-based panel show where multiparty talk is present. Demonstrates a hosts orientation to role in a form of political discourse. Evidence of the way a host 'elicits the news' within the context of a talk show. Illustrates the hybrid nature of political discourse in a televised talk-based program.